mTORC2 REGULATES NEUTROPHIL CHEMOTAXIS IN A cAMP- AND RhoA-DEPENDENT FASHION - Liu, Lunhua (2010)
We studied the role of the target of rapamycin complex 2 (mTORC2) during neutrophil chemotaxis, a process that is mediated through the polarization of actin and myosin filament networks. We show that inhibition of mTORC2 activity, achieved via knock down (KD) of Rictor, severely inhibits neutrophil polarization and directed migration induced by chemoattractants, independently of Akt. Rictor KD also abolishes the ability of chemoattractants to induce cAMP production, a process mediated through the activation of the adenylyl cyclase 9 (AC9). Cells with either reduced or higher AC9 levels also exhibit specific and severe tail retraction defects that are mediated through RhoA. We further show that cAMP is excluded from extending pseudopods and remains restricted to the cell body of migrating neutrophils. We propose that the mTORC2-dependent regulation of MyoII occurs through a cAMP/RhoA signaling axis, independently of actin reorganization during neutrophil chemotaxis.